MAIN DIRECTIONS OF PROTESTS OF THE YOUTH MOVEMENT OF THE 60S OF THE XX CENTURY IN THE UNITED STATES OF AMERICA - Babych, Daria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The purpose of the article is to study the main directions and ideas of the youth movement protests in the United States in the 1960s. Research methods: synthetic, analytical and descriptive, chronological, historical-comparative, retrospective and concrete-historical methods. Results: it is established that the youth movement for the civil rights of African Americans began in the late 1950s. It is concluded that the main consequences of the youth movement in the United States in the 1960s were: the cessation of segregation of African Americans, the expansion of student self-government in universities, the cessation of the escalation of the armed conflict between the United States and Vietnam. It is stated that the US youth movement of the 60s of the twentieth century became an exceptionally large-scale phenomenon in the socio-political and spiritual-cultural spheres of life of the country. Discussion: exploring the main ideas of the US youth movement of the 1960s, the main directions of the movement’s protests were considered, namely: the movement against racial discrimination and for the achievement of civil rights by African Americans; protests for educational reforms; movement against intervention in Indochina. The large-scale sit-in movement and the activities of the Student Coordinating Committee for Nonviolent Action were studied, It was established in 1960 to coordinate student performances on the ground. It was determined that an important component of the youth movement of that time was the “new left movement», which was a new ideological base whose views contradicted the traditional Marxist doctrine of the Communist Parties, and highlighted the events that prompted its emergence. The activity of the organization “Students - for a democratic society», which was established in 1960 on the basis of the Student League, is described. The main ideas and provisions of the Port Huron Declaration of 1962 and three main aspects of the youth movement related to the activities of the organization “Students - for a democratic society». The anti-militarist protests of young people in connection with the US involvement in the armed conflict on the Indochina Peninsula have been studied.